The promotion of ethical coexistence and the prevention of violence in school: considerations about teacher education - Knoener, Darlene Ferraz [UNESP]; Santos, Natalia Cristina Pupin[UNESP]; Duarte, Lidia Morcelli [UNESP] (Unesp-faculdade Ciencias & Letras, 2022)
This investigation objective was to describe and analyze the perceptions of Sao Paulo state management teams and teachers about a proposal for continuing education that integrates a school coexistence program framing. 92 regional education managers, 1440 vice principals and mentoring teachers of coexistence and 5551 regular teachers answered an assessment inspired by rubrics scales. The data indicates that most professionals understand the development of the moral autonomy concepts of the subject's, agree with the feeling recognition work, the need for a cooperative environment, non-violent communication and reciprocal relationships. However, transforming all this into classroom routine practices at school remains a challenge for the majority. The research reinforces the need for spaces for dialogue and reflection in teacher training issues related to coexistence at school.
Keywords: Moral Development; Coexistence at school; Continuing education for teachers; Cohabitation program; Scale training